2020
DOI: 10.6004/jnccn.2019.7385
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impairment, Symptom Burden, and Clinical Outcomes Among Hospitalized Patients With Advanced Cancer

Abstract: Background: National guidelines recommend regular measurement of functional status among patients with cancer, particularly those who are elderly or high-risk, but little is known about how functional status relates to clinical outcomes among hospitalized patients with advanced cancer. The goal of this study was to investigate how functional impairment is associated with symptom burden and healthcare utilization and clinical outcomes. Patients and Methods: We conducted a prospective observational study of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 47 publications
3
46
2
1
Order By: Relevance
“…Existence of edema might also be associated with the progress of anxiety affecting changes of their body images, causing heaviness and disability in daily living as well. This result is consistent with those obtained from an earlier study investigating the association of functional impairment with anxiety 46 . No relation was found between these two factors and the anxiety of their family members.…”
Section: Discussionsupporting
confidence: 93%
“…Existence of edema might also be associated with the progress of anxiety affecting changes of their body images, causing heaviness and disability in daily living as well. This result is consistent with those obtained from an earlier study investigating the association of functional impairment with anxiety 46 . No relation was found between these two factors and the anxiety of their family members.…”
Section: Discussionsupporting
confidence: 93%
“…8,60 In addition, other relevant patient-centered issues to consider assessing in future cancer clinical trials include long-term functional outcomes, financial toxicity, and other patient-reported outcomes. 61,62 The representation of older adults in practice-changing trials in our study was higher than previously reported for cooperative group trials and other analyses, which have generally reported representation of older adults as being between 25% and 35%. 2,4,6 The trials included in our study, given their practice-changing nature and largely industrybased funding, may have attracted or recruited a different population and may have been more appealing to older adults.…”
Section: Discussioncontrasting
confidence: 86%
“…97 (48%) participants were fully independent in basic ADLs, and 59 (29%) were fully independent in instrumental ADLs. 197 (96%) participants had difficulty managing daily activities (median [IQR]) including those fully independent in basic ADLs (48 [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]) or instrumental ADLs (43 [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]) (Figure 3). Only 10% and 5% of participants received physiotherapy or occupational therapy interventions, respectively, within the last month.…”
Section: Resultsmentioning
confidence: 99%
“…48 Consequently, physical and social isolation and reduced rehabilitation threatens a post-COVID-19 wave of disability in people with advanced respiratory disease. Addressing disability is important as it is known to lead to increased hospital stay and discharge to a care facility, 49 putting increased strain on already stretched health-and social-care services. Moving forward, health-and social-care services need to consider post-COVID-19 recovery and rehabilitation for all people deemed extremely clinically vulnerable.…”
Section: Discussionmentioning
confidence: 99%